The Influence of Price, Promotion and Store Atmosphere on Consumer Purchase Decisions of Mie Gacoan in Semarang City - Nanang Adie Setyawan (Al-Kharaj: Journal of Islamic Economic and Business, 2021)
This study aims to analyze the effect of price, promotion and store atmosphere on consumer purchasing decisions of Mie Gacoan in Semarang City . The population used in this study were all customers who had visited and bought Gacoan Noodles in the city of Semarang . This study used confirmatory factor analysis in SEM from the AMOS 24.0 statistical package . The sampling technique in this study used a purposive sampling technique with a sample size of 100 respondents. The data collection method used is the questionnaire method, the data that has been collected is then analyzed using instrument testing, model testing, and hypothesis testing. There are three hypotheses tested in this study, the results of the study indicate that price, promotion and store atmosphere have a positive and significant effect on purchasing decisions.